Efektivitas Mediasi dalam Penyelesaian Perkara Perceraian di Pengadilan Agama Tuban - M. Prima Handa Kusuma; Karmuji Karmuji (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Mediation as an Alternative Dispute Resolution (ADR) is seen as a humanist and fair dispute resolution method. Humanist because the decision-making mechanism (peace agreement) becomes the authority of the disputing parties and maintains good relations. It is fair because each party negotiates a solution to the problem and the output is a win-win solution. Therefore, litigation dispute resolution began to be abandoned and people turned to mediation. Through Supreme Court Regulation (PerMA) No. 1 of 2008, mediation has been integrated into the court system. Every civil case must be resolved first through mediation. Every judge's decision that does not go through mediation first, then the decision is considered null and void. This paper discusses the effectiveness of mediation in the settlement of divorce cases at the Tuban Regency Religious Court, because divorce cases are cases that occupy the highest ranking in the Religious Courts. The focus of the study is the implementation of mediation in divorce cases, the effectiveness of Tuban mediation, what are the obstacles in the implementation of mediation in divorce cases at the Tuban Religious Court.